2006
DOI: 10.1105/tpc.106.041400
|View full text |Cite
|
Sign up to set email alerts
|

Locus-Specific Control of DNA Methylation by theArabidopsisSUVH5 Histone Methyltransferase

Abstract: In Arabidopsis thaliana, heterochromatin formation is guided by double-stranded RNA (dsRNA), which triggers methylation of histone H3 at Lys-9 (H3 mK9) and CG plus non-CG methylation on identical DNA sequences. At heterochromatin targets including transposons and centromere repeats, H3 mK9 mediated by the Su(var)3-9 homologue 4 (SUVH4)/KYP histone methyltransferase (MTase) is required for the maintenance of non-CG methylation by the CMT3 DNA MTase. Here, we show that although SUVH4 is the major H3 K9 MTase, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
296
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(309 citation statements)
references
References 53 publications
12
296
0
1
Order By: Relevance
“…Instead, it appears that the Pol IV transcript is mainly converted into dsRNA or amplified by RDR6, and RDR6-generated dsRNA or amplified transcript is required for DNA methylation. DNA methylation was also unaffected in the ago4/6 double mutant or any of the ago1, 2,3,5,7,8,9 or 10 single mutants, consistent with the hypothesis that 24-nt siRNAs are not required for DNA methylation at this locus ( Figure 1A and Supplementary information, Figure S1C). DNA methylation was also not affected in nrpe1 or nrpb2 mutants ( Figure 1A), indicating that Pol V or Pol II are not required at this locus.…”
Section: Characterization Of An Atypical Rddm Target Locussupporting
confidence: 84%
See 1 more Smart Citation
“…Instead, it appears that the Pol IV transcript is mainly converted into dsRNA or amplified by RDR6, and RDR6-generated dsRNA or amplified transcript is required for DNA methylation. DNA methylation was also unaffected in the ago4/6 double mutant or any of the ago1, 2,3,5,7,8,9 or 10 single mutants, consistent with the hypothesis that 24-nt siRNAs are not required for DNA methylation at this locus ( Figure 1A and Supplementary information, Figure S1C). DNA methylation was also not affected in nrpe1 or nrpb2 mutants ( Figure 1A), indicating that Pol V or Pol II are not required at this locus.…”
Section: Characterization Of An Atypical Rddm Target Locussupporting
confidence: 84%
“…CHG methylation is tightly linked to histone methylation and is maintained by a positive feedback loop. The histone methyltransferases KYP, SUVH5 and SUVH6 bind to methylated CHG and catalyze methylation on histone H3 lysine 9 (H3K9me2) [7][8][9]; the plant-specific DNA methyltransferase CMT3 binds to this mark and promotes CHG methylation [10,11]. The asymmetric CHH methylation is maintained by two different DNA methyltransferases, CMT2 and DRM2.…”
Section: Introductionmentioning
confidence: 99%
“…Naumann et al [91] reported that the N-terminus and YDG domain in SUVH2 are involved in directing DNA methylation and subsequent histone methylation at its target locus so that heterochromatic methylation marks are affected in suvh2 mutant plants. Recently, Ebbs et al [92,93] showed that there is a hierarchical and locusspecific control of H3K9 di-methylation as well as non-CG DNA methylation by SUVH4, SUVH5 and SUVH6 HMT in Arabidopsis. The involvement of this class of proteins in heterochromatin formation was demonstrated for NtSET1 in tobacco [94], and reinforced by the subsequent finding that NtSET1 interacts with LHP1 (Arabidopsis homolog of HP1) [95].…”
Section: Class V: Suppressor Of Variegation [Su(var)] Homologs and Rementioning
confidence: 99%
“…A reinforcing loop between these modifications is suggested by the fact that the chromodomain of CMT3 and the SRA domain of SUVH4 bind H3K9me2 and methylated CHG sites, respectively ( Figure 1b; Lindroth et al, 2004;Johnson et al, 2007). Other histone methyltransferases, including SUVH5 and SUVH6, may be involved in similar reinforcing loops (Ebbs et al, 2005;Ebbs and Bender, 2006). To date it is not known whether the hemi-methylated status of CHG sites after passage of the replication fork serves as an additional cue for maintaining methylation at these sites.…”
Section: Dna Methylation Maintenance Mechanismsmentioning
confidence: 99%